Systematic review using meta‐analyses to estimate dose‐response relationships between iodine intake and biomarkers of iodine status in different population groups. (22nd February 2014) - Ristić‐Medić, Danijela; Dullemeijer, Carla; Tepsić, Jasna; Petrović‐Oggiano, Gordana; Popović, Tamara; Arsić, Aleksandra; Glibetić, Marija; Souverein, Olga W; Collings, Rachel; Cavelaars, Adriënne; de, Lisette; van't, Pieter; et al.
<x xml:space="preserve">Abstract</x> The objective of this systematic review was to identify studies investigating iodine intake and biomarkers of iodine status, to assess the data of the selected studies, and to estimate dose‐response relationships using meta‐analysis. All randomized controlled trials, prospective cohort studies, nested case‐control studies, and cross‐sectional studies that supplied or measured dietary iodine and measured iodine biomarkers were included. The overall pooled regression coefficient (β) and the standard error of β were calculated by random‐effects meta‐analysis on a double‐log scale, using the calculated intake‐status regression coefficient (β) for each individual study. The results of pooled randomized controlled trials indicated that the doubling of dietary iodine intake increased urinary iodine concentrations by 14% in children and adolescents, by 57% in adults and the elderly, and by 81% in pregnant women. The dose‐response relationship between iodine intake and biomarkers of iodine status indicated a 12% decrease in thyroid‐stimulating hormone and a 31% decrease in thyroglobulin in pregnant women. The model of dose‐response quantification used to describe the relationship between iodine intake and biomarkers of iodine status may be useful for providing complementary evidence to support recommendations for iodine intake in different population groups.